Epiphysiolysis Type Salter I of the Medial Clavicle with Posterior Displacement: A Case Series and Review of the Literature - C. Siebenmann; F. Ramadani; G. Barbier; E. Gautier; P. Vial (Case Reports in Orthopedics)
Physeal fractures of the medial clavicle with posterior displacement of the metaphysis are very rare injuries, but additional injuries can be life-threatening. Due to the specific clavicular ossification process, skeletally immature patients present usually not true sternoclavicular joint (SCJ) dislocations accordingly to adults but rather displaced physeal fractures. There is no consensus in the current literature on the best treatment of this lesion. Conservative treatment is not resulting in good outcome; closed reduction is often not successful, and open reduction with internal fixation is finally required. Several methods are described for stabilizing these physeal fractures. We treated three osseous immature patients with this lesion. Due to the small dimension of the medial clavicular epiphysis, we performed in one case a transosseous figure-of-eight suture of the clavicular metaphysis towards the sternum, and in the two other cases, a transosseous suture from the clavicular metaphysis on the anterior clavicular periosteum. The latter technique avoids harm to the small epiphysis or the SCJ and minimizes the risk of retrosternal complications.